A descriptive study to determine the knowledge and practices related to tobacco cessation among clinicians attached to dental colleges in Bangalore City, India - Murthy, Naveen Narasimha; Vanishree, N. (Brazilian Dental Science, 2014)
Objective: Tobacco use cessation is critical in reducing the effect of a major factor for both oral & systemic diseases. Its use continues to be the leading cause of preventable death worldwide with India accounting for probably a large chunk of these, due to its acceptance, both culturally and traditionally. Smoke and smokeless form of tobacco has become steady companion of today’s youth in India. Material and Methods: A descriptive cross-sectional study was conducted to assess the knowledge and practices related to tobacco cessation among practicing dentists a sample size of 366 with inclusion and exclusion criteria attached to various dental colleges in Bangalore city. Results: Comparison of knowledge and practice among qualifications revealed that the knowledge score was more among the MDS professionals with a mean value of 78.3±7.9 and the practice score was also higher among the same with a mean value of 33.3±9. Comparison based on duration of practice revealed that the knowledge score was higher in dentists with experience of 0-5 years by a mean value of 78.4±7.5 and a higher practice score was found in dentists with an experience of 6-8 years with a mean value of 33.5±8.4. Conclusion: Physicians and health care providers in association with their national medical and health professional associations must play a leading role in advocating for the implementation of a comprehensive tobacco control policy and implementation of tobacco cessation methods should be included in the dental curriculum.